Distance education in dentistry in Brazil: a critical STROBE-based analysis - Paulo Goberlânio de Barros SILVA; Camila Costa DIAS; Larissa Carvalho MACHADO; Anna Clara Aragão Matos CARLOS; Thinali Sousa DANTAS; Juliana XIMENES; Renata Mota Rodrigues Bitu SOUSA; Fabrício Bitu SOUSA (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract The COVID-19 pandemic has forced dentistry schools (DSs) to adapt their teaching techniques to digital platforms. Therefore, we aimed to evaluate distance classes in the Brazilian DS curriculum. After an online search of higher education institutions (HEIs) with DS on the e-Ministry of Education (MEC) platform, we included institutions with at least one graduated class to extract the age/localization of the DS, funding, number of authorized seats, MEC-grade, ENADE-score, and workload. HEIs' webpages were consulted to identify the curriculum, subjects offered in the distance education (DE) format, extracurricular programs, scientific events, postgraduate programs, and institutional YouTube channels. Chi-square/Fisher's tests plus binary logistic regression were performed (SPSS 20.0, p < 0.05). Of the 241 DSs evaluated, 82 (34.0%) offered distance classes, and a high prevalence was observed in the southeast region (p <0.001) and private HEIs (p = 0.001). HEIs with distance classes had lower ENADE scores (p = 0.004), lower workload (p = 0.007), and higher workload for optional subjects (p = 0.016), doctoral programs (p = 0.041), specialization courses (p = 0.017), and institutional YouTube channels (p < 0.001). Southern dental schools (p < 0.001), lower workload (p = 0.022), optional subjects (p = 0.033), and institutional YouTube channels (p = 0.005) were independently associated with distance classes. In one-third of the Brazilian DSs, distance classes and institutional YouTube channels were strongly associated variables. The association of distance learning with lower workload and low academic performance draws attention to the need for regulatory bodies for controlling the quality of DE.